Adverse outcome of acute splenic sequestration crisis in pregnancy. (June 2021) - Malinowski, Ann Kinga; Parrish, Jacqueline; D'Souza, Rohan; Kuo, Kevin HM; Ward, Richard; Shehata, Nadine
Background: Acute splenic sequestration crisis, characterized by abrupt fall in hemoglobin, splenomegaly, hypovolemia, and often thrombocytopenia, occurs infrequently in adults with sickle cell disease and extremely rarely during pregnancy. Case: A 25-year-old woman with HbSC presented at 33 weeks' gestation with vaso-occlusive pain. Sudden worsening of abdominal pain and non-reassuring fetal surveillance on day 3 of admission led to emergent delivery. Acute splenic sequestration crisis was the diagnosis of exclusion based on clinical presentation and intra-operative hemoglobin of 37 g/L. Five- and 10-minute Apgar scores were 4. Neonatal brain magnetic resonance imaging revealed significant diffuse white matter abnormalities. Conclusion: Acute splenic sequestration crisis in pregnancy must be considered in the differential diagnosis for this patient population as it can evolve rapidly and lead to maternal and fetal compromise.